Pengembangan Kreativitas Hasta Karya Melalui Mewarnai di TK Blessing Kids Yayasan Amazing Grace - Marwah, Aulia; Pefrianti, Indah; Sihite, Erika br; Silalahi, Wilde Dosta Cristina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to develop early childhood creativity through coloring activities as part of handicrafts at Blessing Kids Kindergarten. Coloring is one of the effective activities in stimulating children's creativity, imagination, and fine motor skills. This research employs a qualitative method with data collection techniques including observation, interviews, and documentation. The coloring activities involve the use of various media and techniques designed to provide children with the freedom to express themselves. The results of the study show that the children experienced improvements in creativity, color selection abilities, and imagination after actively participating in the coloring activities. These findings indicate that coloring is an effective way to develop handicraft creativity in kindergarten. This study recommends that coloring activities be more frequently applied in kindergartens as an enjoyable and educational learning method.